Breast Cancer Management and Molecular Medicine - Piccart, Martine J.; Piccart, Martine J.; Wood, William C.; Wood, William C.; Hung, Chie-Mien.; Hung, Chie-Mien.; Solin, Lawrence J.; Solin, Lawrence J.; Cardoso, Fatima.; Cardoso, Fatima. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Molecular-based medicine is taking center stage due to the increasing knowledge of breast cancer molecular biology. Treatment tailoring is no longer a dream for the future, but the main goal of current research. This book provides an overview of the most recent techniques, agents and approaches for breast cancer that contribute to the individualization of treatment. Current biomedical research focuses on facilitating the transfer of molecular biology knowledge into the clinical management of patients, leading to increased survival as well as improved quality of life. Particular attention is given in this book to organ-specific tailored approaches, specific populations, patients’ preferences and rehabilitation. Also discussed in depth are the respective roles of pharmacotherapeutics modelling, functional imaging, molecular staging, genomics and proteomics and their impact on the "re-classification" of breast cancer, as well as the clinical applications of basic science. The crucial issue of how to optimally integrate biological markers, new technologies and new diagnostic and therapeutic approaches into clinical trials and clinical practice is addressed. Combining the contributions from authors who are well known experts in these fields with editorial comments, this book provides an overview of the latest achievements in breast cancer and their use in clinical practice.